Tajikistan : Reinvigorating Growth in Khatlon Oblast - Carneiro, Francisco (World Bank, Washington, DC, 2014)
This report supports a joint World Bank-IFC initiative to review and evaluate economic growth prospects for Khatlon oblast in order to develop a private sector-driven strategy for accelerating the region's growth over the medium term.